(untitled) (Journal of the College of Basic Education, 2020)
The current research aims to identify "the effect of the Van Hill model in developing reading comprehension among students of class The fourth in the critical reading article "The researchers put the hypothesis of zero vs. the alternative hypothesis follows There are no statistically significant differences at the level of significance (0.05) between the average scores of the experimental group In the development of critical reading skills before applying the Van Hill model and during the application of the test appeared to be there The difference is statistically significant since the value T calculated at the level of significance (0,05) and degree of freedom (32) is Greater than the T-table value and thus reject the null hypothesis and accept the alternative: The research also found that the model had a positive impact on raising the level of cash for the readable text Fourth-grade students more than the traditional method, because of the current research showed superiority The experimental group on the control group In light of the result, the following can be inferred: To complement the research procedure, further studies are proposed to conduct a similar study of the model in the fourth-grade preparatory reading.